Hyperperfusion on Arterial Spin Labeling MRI Predicts the 90‐Day Functional Outcome After Mechanical Thrombectomy in Ischemic Stroke - Lu, Shan‐shan; Cao, Yue‐zhou; Su, Chun‐qiu; Xu, Xiao‐quan; Zhao, Lin‐bo; Jia, Zheng‐yu; Liu, Qiang‐hui; Hsu, Yi‐cheng; Liu, Sheng; Shi, Hai‐bin; Wu, Fei‐yun (Journal of magnetic resonance imaging, 2021)
Background The prognostic significance of hyperperfusion after reperfusion therapy in patients with acute ischemic stroke (AIS) remains controversial. Purpose To investigate the clinical factors associated with hyperperfusion, and the 90‐day prognostic value of hyperperfusion after mechanical thrombectomy in AIS patients. Study Type Retrospective. Population/Subjects Fifty‐four AIS patients who underwent mechanical thrombectomy. Field Strength/Sequence Time‐of‐flight MR angiography, pulsed arterial spin labeling (ASL), diffusion‐weighted imaging (DWI), and susceptibility‐weighted imaging were performed at 3.0T within 1 week after thrombectomy. Assessment Clinical factors including demographics, risk factors, stroke and treatment characteristics were collected and assessed. Hyperperfusion on ASL was defined as a focal increased cerebral blood flow on the affected side ≥130% of its mirror counterpart. Good clinical outcome at 90 days was defined as modified Rankin Scale score of 0–2. Statistical Tests The interrater agreement was assessed using Cohen's kappa or the intraclass correlation coefficient. The relationship between hyperperfusion and clinical factors were analyzed by appropriate univariate statistics. Predictors of 90‐day functional outcome were assessed by univariate analyses followed by multivariate logistic regression analysis and receiver‐operating‐characteristic curves. Results Thirty‐six (66.7%) patients developed hyperperfusion on ASL after thrombectomy. Hyperperfusion was significantly correlated with successful recanalization (P < 0.05) and improvement of National Institutes of Health Stroke Scale scores at 24 hours (NIHSS24h) (P < 0.05). A higher incidence of hemorrhage transformation was observed in patients with hyperperfusion than those without (63.9% vs. 50.0%), but no significant difference was found (P = 0.327). NIHSS24h (odds ratio [OR], 0.75, [95% confidence interval [CI] 0.62–0.91], P < 0.05), lesion volume on diffusion‐weighted imaging (OR, 0.97, [95% CI 0.95–1.00], P < 0.05), and hyperperfusion on ASL (OR, 9.8, [95% CI 1.7–55.3], P < 0.05) were independent variables for predicting good functional outcomes. Data Conclusion Hyperperfusion on ASL correlated with successful recanalization and may be an independent prognostic marker for good neurological outcomes at 90 days in AIS patients after mechanical thrombectomy. Level of Evidence 4 Technical Efficacy Stage 2